PENGUATAN SISTEM INFORMASI ADMINISTRASI PEMERINTAH DESA DAN APLIKASI KEPENDUDUKAN ONLINE NEW GENERATION DI KABUPATEN BULELENG - I Made Darsana (Publikasi Ilmiah Bidang Pengabdian Kepada Masyarakat (SIKEMAS), 2023)
The development of information and communication technology (ICT) has changed the paradigm of public services in various countries, including Indonesia. ICT is the main key in increasing the efficiency, transparency and accessibility of public services, as well as encouraging the active participation of the community in the development process. In this digital era, innovation and the use of technology in the public sector are important to ensure efficient and quality services. Through the integration of administrative information systems, regional governments can support effectiveness and openness in public services. Integrating local government administrative information systems has a strategic role in improving service quality. Thus, the regional government in Buleleng Regency has responded to the dynamics of the digital era by implementing AKUOnline-NG (Integration of Village Government Administration Information Systems and the New Generation Online Population Application). AKUOnline-NG is an innovative solution that brings together technological sophistication with the need for better community services at the village level. Community service activities from IPB International in collaboration with the Buleleng Regency Civil Registration Service have successfully implemented AKUOnline-NG. Through the stages of identifying needs, system development, outreach, training, as well as implementation and monitoring, this system has succeeded in increasing the efficiency of the bureaucracy and the quality of public services in the targeted villages. This system integrates village government administration with online population applications, providing benefits in the form of time and cost efficiency, accuracy of population data, and active community participation in the development process.